Aesthetic Treatment Of Maxillary Central Diastema Due To Differences In Teeth And Jaw Sizes With Removable Orthodontics - Muhamat Muhtar S. Abdurrohman; Saskia Aida Hidayat; Christina Mahardika; Rama Putranto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: The aesthetic treatment of maxillary central diastema due to differences in tooth and jaw size is an important component of orthodontic treatment. Tooth size and shape are crucial factors that affect the smile and face in treatment results. From an orthodontic perspective, evaluating the ideal mesiodistal width of teeth in relation to the upper and lower jaw arches is necessary to plan for proper occlusion, aesthetics, and functionality.Case: A 19-year-old woman came to RSIGM Sultan Agung complaining that her upper front teeth appeared spaced apart and affected her appearance. The patient's medical history showed that he was in good general health. Extraoral examination was within normal limits. Intraoral examination revealed a diastema between the upper central incisors, normal frenulum attachment, an overjet of 3.4 mm, and an overbite of 3.1 mm. Analysis of the working model revealed a positive arch length discrepancy in the upper jaw, while other analysis results were within normal limits. The etiology of the diastema in this case was the size of the available dental arch and normal tooth size. The patient underwent treatment for central diastema using removable orthodontic appliances equipped with active and passive devices, as well as additional finger spring components to mesialize teeth 11 and 12 and close the maxillary central diastemaConclusion: Esthetic treatment of maxillary central diastema caused by differences in tooth and jaw size can be performed using removable orthodontic appliances with additional finger spring components. Patient cooperation during treatment and retention appliances are necessary to achieve stable long-term orthodontic results